Developing a Smart Apps Creator Application Using the Institution Word Method to Enhance Early Reading Skills in Young Learners - Zakiyyah, Auji Zahrotuz; SB, Nugraheti Sismulyasih (JOLLT Journal of Languages and Language Teaching, 2025)
Good reading skills are in demand for elementary school students, but the facts in the field prove that elementary school students' initial reading is still relatively low. So, this is a challenge that can cause learning difficulties. Learning media is still not optimally used during the learning process. This research aims to develop, test the feasibility, and test the results of the effectiveness of the smart app creator educational application media using the institutional word method to improve the initial reading skills of grade 1 school students. This research uses Research and Development (R&D) created by Sugiyono. The test subjects were 22 students of class 1A SDN kalibanteng Kidul 03 Semarang City. The smart app creator application consists of several components: the star page, instructions for use, main menu, introduction menu, material menu, quizizz menu, let us try the menu, practice menu, and developer profile menu. This study's results show the feasibility test results of 93% of media experts and 96.15% of material experts with very feasible criteria. The results of the media effectiveness test using the paired test obtained a significant value of <0.001. The result of the N-Gain calculation was obtained with a value of 0.7277 in the high category. Therefore, the study's can be concluded that the smart app creator educational application using the institutional word method is feasible and effective in improving the initial reading skills of grade I students.